2016
DOI: 10.1111/jan.13053
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge expectations of recently diagnosed patients with knee osteoarthritis

Abstract: Patients with knee osteoarthritis have high knowledge expectations and there is a need to improve the counselling and care of pain and tiredness or fatigue symptoms. The development of the counselling of recently diagnosed patients with knee osteoarthritis also needs further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 49 publications
(128 reference statements)
0
20
0
Order By: Relevance
“…The descriptive characteristics of the included studies is shown in Table 1 . The majority of studies were conducted in the United Kingdom[ 25 , 30 , 35 , 36 , 39 , 42 , 44 , 47 , 49 , 50 ], with the remainder from Europe[ 22 , 26 , 28 , 31 , 32 , 37 , 41 , 45 , 46 , 48 ], North America[ 27 , 33 , 43 , 51 ], South-East Asia[ 29 , 40 ], Australia[ 38 ], Middle-East[ 23 ] and an unknown source[ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The descriptive characteristics of the included studies is shown in Table 1 . The majority of studies were conducted in the United Kingdom[ 25 , 30 , 35 , 36 , 39 , 42 , 44 , 47 , 49 , 50 ], with the remainder from Europe[ 22 , 26 , 28 , 31 , 32 , 37 , 41 , 45 , 46 , 48 ], North America[ 27 , 33 , 43 , 51 ], South-East Asia[ 29 , 40 ], Australia[ 38 ], Middle-East[ 23 ] and an unknown source[ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants were classified as having OA using American College of Rheumatology (ACR) criteria in 3 studies[ 29 , 32 , 34 ], radiographic change and pain in 4 studies[ 30 , 40 , 44 , 49 ], self report in 6 studies[ 24 , 27 , 35 , 39 , 43 , 47 ], chart review in 3 studies[ 31 , 33 , 46 ], clinical diagnosis in 4 studies[ 36 , 37 , 42 , 48 , 50 ], and by undefined methods in 8 studies[ 22 , 23 , 26 , 28 , 38 , 41 , 45 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in our study had demonstrated knowledge on the clinical presentation of KOA having lived with the condition for more many years. Previous reports have reported a desire among individuals living with KOA for more knowledge particularly about the management of related symptoms [30,70]. Providing sufficient information about KOA to clients are particularly vital in supporting decision-making, promoting positive behavioral changes and improving health outcomes [71][72][73].…”
Section: Plos Onementioning
confidence: 99%